Ad Hominem Criminalisation and the Rule of Law: The Egalitarian Case against Knife Crime Prevention Orders. (28th December 2021) - Green, Alex; Hendry, Jennifer
Abstract: This article advances a novel account of ad hominem criminalisation that draws upon a distinct theory of the Rule of Law and its egalitarian foundations. Employing the recent and controversial example of Knife Crime Prevention Orders, as established by the Offensive Weapons Act 2019, it argues that the concept of civic equality is central to understanding the vice of ad hominem criminalisation as an aberrant form of government by law. This vice consists in the manner that such criminalisation individualises, differentiates and instrumentalises the regulatory subject, placing them outwith the bounds of civic equality as established by the Rule of Law.